Old school friends: former social relationship patterns in a long dream series - Schredl, Michael (International journal of dream research, 2012)
Social interactions are very common theme in dreams. The present study based on a dream series of 7,747 dreams investigated the long-term effect of the dreamer’s social pattern during school years on his adult dreaming. Overall, school-related dreams were found even 20 years after graduation. For the social pattern, personal significance and time spent together seems to be the main factor explaining the frequency of former schoolmates in dreams. To extend this single-case study, it would be fruitful to study similar dream series in order to shed light on the long-term effects of waking life on dreaming.